2015
DOI: 10.1002/ijc.29881
|View full text |Cite|
|
Sign up to set email alerts
|

Combination therapy with zoledronic acid and cetuximab effectively suppresses growth of colorectal cancer cells regardless of KRAS status

Abstract: Targeted molecular therapy is an effective anticancer strategy. Anti‐EGFR monoclonal antibodies such as cetuximab (CTX) have been approved for the treatment of various malignancies, including colorectal cancer (CRC) with wild‐type KRAS. However, their efficacy in patients with KRAS mutations has not been established. Therefore, we investigated whether CTX treatment was effective as a single agent or in combination with zoledronic acid (ZOL) in human CRC cell lines with different KRAS status. CRC cell lines SW4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…We previously reported that the addition of zoledronic acid to anti-EGFR therapy results in tumor-growth suppression, even in KRAS -mutated CRC cells 41 . This strategy can correct both the AKT- and MAPK-signaling pathways and enhance the effect of anti-EGFR therapy, and it is possible that this additional treatment might help to enhance the effects of anti-GPNMB and anti-EGFR/HER2 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that the addition of zoledronic acid to anti-EGFR therapy results in tumor-growth suppression, even in KRAS -mutated CRC cells 41 . This strategy can correct both the AKT- and MAPK-signaling pathways and enhance the effect of anti-EGFR therapy, and it is possible that this additional treatment might help to enhance the effects of anti-GPNMB and anti-EGFR/HER2 therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments showed that Ixazomib elicited a significant growth-inhibitory effect in both colorectal cell lines, as evidenced by a reduction in cell viability in vitro and the reduction of tumor growth rates in vivo . SW1222 tumors were found to be more sensitive to Ixazomib than LS174T tumors, which could be due to their different K-Ras mutations: SW1222 cells have a K-Ras mutation at A146V 35 , compared with G12D for LS174T tumors 36 , which has been proposed to infer a greater sensitivity to proteasome inhibition 9 . In addition, the microenvironment of the two tumor types could provide a source of resistance in vivo , with LS174T tumors being less vascular, less differentiated and less perfused than SW1222 tumors 37 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Our experiments showed that ixazomib elicited a significant growth-inhibitory effect in both colorectal cell lines, as evidenced by a reduction in cell viability in vitro and in the reduction of tumor growth rates in vivo. SW1222 tumors were found to be more sensitive to ixazomib than LS174T tumors, which could be due to their different K-Ras mutations: SW1222 cells have a K-Ras mutation at A146V (35), compared with G12D for LS174T tumors (36), which has been proposed to infer a greater sensitivity to proteosome inhibition (11). In addition, the microenvironment of the two tumor types could provide a source of resistance in vivo, with LS174T tumors being less vascular, less differentiated and less perfused than SW1222 tumors (37-39).…”
Section: Discussionmentioning
confidence: 99%